The effect of foreign direct investment and remittances on trade balance in BRICS countries : panel data analysis - Mohloana, Phuti (My University, 2025)
The study examined the effect of foreign direct investment (FDI) and remittances on BRICS countries trade balance spanning yearly data from 2001 to 2019. Employing econometric techniques such as Panel Autoregressive Distributive Lag (PARDL), Engel-Granger causality test and accounting innovations. The findings of PARDL revealed a significant negative effect on the trade balance in the long run. Yet a positive but insignificant effect in the short run. A favourable insignificant association was revealed between remittances and the trade balance in the long run, proving the absence of the Dutch Disease in BRICS countries. However, a positive effect but insignificant in the short run. The findings of Engel-Granger causality test revealed a unidirectional causal association between FDI and the trade balance. However, no sign of causality between remittances and the trade balance. Furthermore, the model’s variables primarily experience shocks from internal innovations, demonstrated by impulse response function and variance decomposition test.
Thesis (M. Com. (Economics)) -- University of Limpopo, 2024
Keywords: BRICS; FDI; Remittances; Trade Balance; Dutch Disease; Accounting Innovations; Investments, Foreign; Balance of trade; BRIC countries